Multisectorial changes in the ciliary muscle during accommodation measured with high-resolution optical coherence tomography - Monsálvez-Romín,Daniel (2019)
ABSTRACT Purpose: To measure changes in the anterior ciliary muscle during accommodation at the nasal, superior, temporal, and inferior sectors by means of an anterior chamber optical coherence tomographer, and correlate them with vergence changes. Methods: Twenty-four subjects with healthy, phakic eyes, whose mean age was 27.1 ± 8.9 years, underwent measurement with an anterior chamber optical coherence tomographer. The anterior ciliary muscle was measured at the nasal, temporal, superior, and inferior sectors for 0, -1, -2, and -3 D of vergence. A linear model was used to assess the correlation of each eye parameter with the accommodative demand. Results: The anterior ciliary muscle area significantly increased with accommodation for each sector, with a maximum increase of about 30% for the nasal-temporal sectors and about 25% for the inferior-temporal sectors. The linear model showed a tendency toward a positive relationship between change in the ciliary muscle area of each sector and vergence. Conclusion: The anterior ciliary muscle area tends to increase with accommodation, although the increase has been shown to be symmetric between the pair sectors superior-nasal and inferior-temporal. These results may help to increase understanding of accommodation biometry and biomechanics.